Notes on Ethnical Components in Forming Archeological Picture of Southwestern Serbia and Northern Montenegro in Prehistory and Early Roman Period - Ljuština, M.; Cvijetić, J. (Археологія і давня історія України, 2019)
The paper is devoted to recognition of ethnical components and their importance in creation of archaeological picture of South-Western Serbia and Northern Montenegro in proto-history and Early Roman period. The chosen region was an integral part of the Illyrian world, but on the threshold of the Thracian at the end of later prehistory. As for the subsequent period of Roman domination, one of the most important tasks for the future exploration is at least partial enlightening the structure of the population the Romans found in this area at the turn of the Christ Era. Either the new era or the Christian era.